Insecticidal efficacy of essential oil from Cinnamomum zeylanicum Blume and its two major constituents against Callosobruchus maculatus (F.) and Sitophilus oryzae (L.) - Brari, J.; Thakur, D. R. (International Journal of Agricultural Technology, 2015)
Essential oil isolated from Cinnamomum zeylanicum Blume was analyzed by mass spectroscopy (MS) and two of its main constituents were identified. Contact and fumigant activity of C. zeylanicum essential oil and its two constituents viz., cinnamaldehyde and linalool were examined against two stored product pests, Callosobruchus maculatus F. (Coleoptera: Bruchidae) and Sitophilus oryzae L. (Coleoptera: Curculionidae). Responses varied with respect to doses of compounds, insect species and exposure time. In contact activity assay, the cinnamon oil at 1.2 mg/cm2caused 98 and 80% mortality against C. maculatus and S. oryzae adults respectively, after 24 hours of treatment. 0.3 mg/cm2 of cinnamaldehyde caused 100 % mortality in C. maculatus whereas, similar dose of linalool caused 89% mortality in S. oryzae after an exposure period of 12 hrs. The fumigant action as compared to contact toxicity indicated high percentage of mortality for adult insects even at low doses of compounds and less duration of exposure. The essential oil of cinnamon along with its major constituents demonstrates higher contact and fumigant toxicity to C. maculatus than S. oryzae adults. Further, cinnamaldehyde showed higher toxicity than linalool and it may be attributed to its chemical structure.